Efektivitas Penegakan Hukum Tindak Pidana Judi Online di Kalangan Mahasiswa - Khalimy, Akhmad; Avissa, Avrilia Aurelia; Apriyanti, Afia; Triastuti, Rini (Bacarita Law Journal, 2025)
Online gambling has become a global phenomenon, especially because of its easy access so that it can be reached by various groups, including students. The purpose of this study was to determine the factors that cause students to use online gambling and the obstacles to enforcing online gambling among students. This study uses a descriptive qualitative research type with a sociological legal approach. The results of the study indicate that several factors that encourage students to play online gambling are basically related to economic factors, perceptions of winning opportunities, boredom, friendships, and venting. The variety of these factors shows that many students are caught in online gambling. The biggest obstacle in enforcing the law on online gambling crimes comes from the awareness of the students themselves. Among them, some feel safe playing online gambling because of anonymity, minimal law enforcement, and some are even aware of the criminal risks but still play. Therefore, the relevant parties are deemed necessary to make several preventive efforts aimed at preventing the occurrence of gambling crimes. Strengthening legal regulations, especially by expanding the scope of online gambling crimes, will ensure that all parties involved in online gambling can be subject to appropriate sanctions. Active and targeted socialization will increase students' awareness of the dangers and consequences of online gambling, while financial literacy programs will help students to be wiser in managing their finances and avoid the risk of falling into gambling. With the combination of these three efforts, it is hoped that an environment free from the negative influence of online gambling will be created for students.